2007
DOI: 10.1074/jbc.m604440200
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Structural and Functional Properties of D-domain Containing Redox-active and -inactive Protein Disulfide Isomerase-related Protein Chaperones

Abstract: The structure and mode of binding of the endoplasmic reticulum protein disulfide isomerase-related proteins to their substrates is currently a focus of intensive research. We have recently determined the crystal structure of the Drosophila melanogaster protein disulfide isomerase-related protein Within the endoplasmic reticulum (ER), 3 an optimal protein folding environment (1) essential for many secretory proteins is provided by a battery of ER chaperones and folding factors, including the chaperones calnexin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 24 publications
4
17
0
Order By: Relevance
“…When the LE was incubated with a cross-linker and then immunoblotted with an antibody against ERp29 (ϳ30 kDa), a ϳ60 kDa band appeared, indicating the formation of an ERp29 homodimer ( Figure 1B, cf. lane 2 to 1), consistent with previous reports (Mkrtchian et al, 1998b;Ferrari et al, 1998;Lippert et al, 2007). Similarly, when purified ERp29 NTD (ϳ17 kDa) was incubated with a cross-linker, a ϳ35-kDa species appeared ( Figure 1B, cf.…”
Section: Erp29 and Erp29 Ntd Form A Heterodimersupporting
confidence: 91%
See 1 more Smart Citation
“…When the LE was incubated with a cross-linker and then immunoblotted with an antibody against ERp29 (ϳ30 kDa), a ϳ60 kDa band appeared, indicating the formation of an ERp29 homodimer ( Figure 1B, cf. lane 2 to 1), consistent with previous reports (Mkrtchian et al, 1998b;Ferrari et al, 1998;Lippert et al, 2007). Similarly, when purified ERp29 NTD (ϳ17 kDa) was incubated with a cross-linker, a ϳ35-kDa species appeared ( Figure 1B, cf.…”
Section: Erp29 and Erp29 Ntd Form A Heterodimersupporting
confidence: 91%
“…Mutation of D42 to alanine presumably disrupted the hydrogen bond, leading consequently to a marked loss of dimer stability. Consistent with our observation that the D42A rat ERp29 mutant failed to dimerize, the corresponding D31N mutant in Wind (Ma et al, 2003) and the D42N mutant of human ERp29 (Lippert et al, 2007) are also significantly defective in dimerization.…”
Section: The D42a Erp29 Mutant Dimerizes Inefficientlysupporting
confidence: 91%
“…Studies of the ERp29 D. melanogaster orthologue, Wind, have shown that five residues in the CTD of Wind (E212, R215, R218, L219, and L232) contribute to its ability to chaperone the secretory substrate, Pipe, from the ER to the Golgi compartment (1). Furthermore, when fused to the NTD of Wind, the CTD of mouse ERp29 can functionally replace the corresponding Wind domain, and mutations corresponding to the ERp29 CTD residues (E220Q, R223A, K226E, L227S, and L240K) disrupt the chaperone activity of the Wind-ERp29 hybrid (10,11). We therefore asked whether these residues in ERp29 CTD might play a role in mediating PyV unfolding.…”
Section: Resultsmentioning
confidence: 99%
“…Although the function of the ERp29 CTD (which consists of helices ␣5 to ␣9) has not been established, Wind CTD has been demonstrated to play a critical role in Wind's chaperone activity, possibly serving as a substrate-binding site (1,10). This finding raises the possibility that the ERp29 CTD may similarly play a crucial role during the PyV unfolding reaction.…”
mentioning
confidence: 99%
“…This is especially important as variant dimerization models for the b domain and dramatically different tertiary structures of the D domains of mammalian orthologs compared to Wind have been suggested and have been interpreted as an indication of variant functional roles of the two proteins. [16][17][18] NMR structures of the individual b and D domains of rat ERp29, reported by Liepinsh et al, 16 indicated involvement of residues Asp71, Phe118, Arg122, Asp123, and Trp144 in dimerization. Furthermore, a conserved proline residue, Pro116, found in the a domains of most PDI proteins in cis conformation, where it plays a structurally and possibly functionally important role, was suggested to be in trans conformation in ERp29, indicating gross structural and functional differences in this domain beyond the variant dimerization properties.…”
Section: Introductionmentioning
confidence: 98%